INFLUENCE OF MATERIAL DAMPING ON THE RESPONSE OF UNDERGROUND STRUCTURES SUBJECTED TO EARTHQUAKE - Veronika Pavelcová; Tereza Poklopová; Michal Šejnoha; Tomáš Janda (Acta Polytechnica CTU Proceedings, 2020)
The paper describes a finite element simulation of the response of a real underground structure subjected to earthquake using GEO5 FEM program. It concentrates on the influence of material damping with respect to a specific type of boundary condition prescribed at the bottom of the analyzed domain. It is seen that considering material damping is inevitable particularly in case of so called fixed boundary conditions to arrive at meaningful results. This is demonstrated on an artificial earthquake generated according to a design spectrum defined in Eurocode 8. A viscous damping ratio combined with the results of eigenvalue analysis is used to derive parameters of Rayleigh damping for three specific scenarios promoting the approach based on the lowest natural frequency as sufficiently accurate for the present task.